ANALISIS YURIDIS TERHADAP PELAKSANAAN PARATE EKSEKUSI HAK TANGGUNGAN ATAS KREDIT MACET PADA PT. BANK SUMUT (Studi Putusan Pengadilan Negeri Medan No.167/Pdt.G/2013/PN.Mdn jo Putusan Pengadilan Tinggi Medan No.270/PDT/2014/PT-MDN) - ADELIA NOVRIANI PURBA (PREMISE LAW JURNAL, 2016)
The parate execution can be really cancelled if there is a lawsuit from the third party on the plan for the implementation of foreclosure sale as stipulated in Article 27, point c of the Decree of the Minister of Finance No.93/PMK.06/2010 on the Operational Manual of Auction, this condition is also experienced by PT. Bank Sumut in the implementation of parate execution. The research used judicial normative and descriptive analytic methods. The regulation on the implementation of parate execution of collateral in the Indonesian legal provision is still based on Article 224 of HIR and Article 258 RBg. The obstacle in the implementation of parate execution of collateral at PT. Bank Sumut comes from substantial aspect, the structural aspect and legal cultural aspect. The Ruling of the Medan District Court No.167/Pdt.G/2013/PN.Mdn juncto the Ruling of the Higher Court of Medan No.270/PDT/2014/PT-MDN states that PT Bank Sumut does not violate law. Keywords: Parate Execution, Parate Execution of Collateral, Credit